2013
DOI: 10.3346/jkms.2013.28.6.908
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Hepatitis A Infection in Korea in 2007 and 2009: A Case-Control Study

Abstract: This study aimed to identify the risk factors associated with acute hepatitis A virus (HAV) infection in the Korean population. Participants were recruited from five referral hospitals across the country in 2007 and from 11 hospitals in 2009. Patients with positive anti-HAV IgM antibody tests became the case group, while patients treated for non-contagious diseases at the same hospitals were recruited as controls. A total of 222 and 548 case-control pairs were studied in the 2007 and 2009 surveys, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
(44 reference statements)
3
26
0
1
Order By: Relevance
“…This result is consistent with the reported age-specific seroprevalence rate in Korea [11,12], as the high seroprevalence in individuals <10 years of age is related to vaccination that was introduced in 1997 [4], and the high seroprevalence in individuals >40 years of age is related to childhood infections that occurred before Korea’s rapid socioeconomic development and public sanitation improvements [11-13]. Therefore, hepatitis A occurred most frequently in the 20-39-year-old group, who exhibited a low seroprevalence rate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with the reported age-specific seroprevalence rate in Korea [11,12], as the high seroprevalence in individuals <10 years of age is related to vaccination that was introduced in 1997 [4], and the high seroprevalence in individuals >40 years of age is related to childhood infections that occurred before Korea’s rapid socioeconomic development and public sanitation improvements [11-13]. Therefore, hepatitis A occurred most frequently in the 20-39-year-old group, who exhibited a low seroprevalence rate.…”
Section: Discussionsupporting
confidence: 91%
“…This economic development and concomitant improvements in public sanitation have altered the epidemiology of hepatitis A in Korea, and the endemicity of hepatitis A has changed from high to intermediate [10]. In this context, various studies have evaluated the incidence, seroprevalence, risk factors, and vaccination status for hepatitis A [3,4,11-15], and have reported high incidence rates among individuals who are 20-39 years old. Nevertheless, it is likely that recent changes in age cohorts, vaccination status, lifestyle, and overseas travel have influenced the incidence of hepatitis A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that eating raw shellfish was shown to be a significant predictor of HAV infection in the multivariate analysis [21] and eating raw shellfish significantly increased the odds ratio of HAV infection in an Italian study [22]. As reported from other parts of the world, most studies support the correlation between eating raw shellfish and the risk of hepatitis A infection [2] [17] [23] [24].…”
Section: Discussionmentioning
confidence: 52%
“…In 2007, the Korean Society of Infectious Diseases recommended that all adults in their 20s should be vaccinated against hepatitis A, as well as adults in their 30s and 40s without immunity [46]. It should be noted that immunization for adult who is likely to eat raw oyster or handle food ingredients occupationally or travel overseas to HAV-endemic areas is needed to prevent spreading from an outbreak caused by HAV [21].…”
Section: Discussionmentioning
confidence: 99%